2023
DOI: 10.1021/acsomega.2c06931
|View full text |Cite
|
Sign up to set email alerts
|

Study on Growth Influencing Factors and Desulfurization Performance of Sulfate Reducing Bacteria Based on the Response Surface Methodology

Abstract: Sulfate reducing bacteria (SRB) can simultaneously and efficiently remove SO 4 2− and heavy metal ions from acid mine drainage (AMD). Environmental factors have a great influence on AMD treated by SRB metabolic reducing sulfate. Providing a suitable growth environment can improve the effect of SRB on AMD. In this paper, the wet soil around the tailings reservoir was used as seed mud to enrich SRB. Based on the single factor experiment method and the response surface methodology (RSM), the effects of temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Under each temperature condition, the pH of the solution showed a gradual increase with the growth of the bacterial strains, with the most significant increase observed at 30 • C (Figure 3a). This is mainly because SRB exhibit high growth activity and a large population size at this temperature, resulting in higher metabolic alkalinity [26]. Figure 3c indicates that the OD600 value of the solution was lowest at 20 • C and highest at 30 • C, further suggesting optimal SRB growth conditions at this temperature, which is consistent with the findings reported by Sokolova [27].…”
Section: The Influence Of Initial CD 2+ Concentration On the Immobili...supporting
confidence: 87%
See 1 more Smart Citation
“…Under each temperature condition, the pH of the solution showed a gradual increase with the growth of the bacterial strains, with the most significant increase observed at 30 • C (Figure 3a). This is mainly because SRB exhibit high growth activity and a large population size at this temperature, resulting in higher metabolic alkalinity [26]. Figure 3c indicates that the OD600 value of the solution was lowest at 20 • C and highest at 30 • C, further suggesting optimal SRB growth conditions at this temperature, which is consistent with the findings reported by Sokolova [27].…”
Section: The Influence Of Initial CD 2+ Concentration On the Immobili...supporting
confidence: 87%
“…Under each temperature condition, the pH of the solution showed a gradual increase with the growth of the bacterial strains, with the most significant increase observed at 30 °C (Figure 3a). This is mainly because SRB exhibit high growth activity and a large population size at this temperature, resulting in higher metabolic alkalinity [26]. Microbial cell growth involves a series of enzyme−catalyzed reactions, and excessively high or low temperatures can inhibit the activity of certain enzymes in these cells.…”
Section: The Influence Of Initial CD 2+ Concentration On the Immobili...mentioning
confidence: 99%
“…This showed that a high density of bacteria caused a lower concentration of sulfur, temperature, conductivity, and DO. The results showed that environmental factors affected the activity of enzymes in bacteria, thereby influencing the efficiency of SOB in treating sulfur (Dong et al, 2023). The results of the Venn analysis obtained in Figure 4 showed that coal post-mining ponds samples with age of > 20 years had more OTUs when compared to those aged < 5 years.…”
Section: Water Quality Profile From Post-mining Ponds Water In Samarindamentioning
confidence: 95%
“…The process can occur with or without agitation and aeration through diffusion (shaker incubator with orbital shaking and heating). Dong et al (2023) used Erlenmeyer flasks to monitor the growth of SRB. These bacteria exhibited an "S-"type growth curve, and their logarithmic growth phase was quantified throughout 14-86 h, demonstrating high activity and robust growth metabolism.…”
Section: Sulfate-reducing Bacteria and Operating Conditions In Biorea...mentioning
confidence: 99%